The Politics of Post-Suharto Indonesia (Council on Foreign Relations Press, 1999)
This book responds to the critical need of policymakers, practitioners, and scholars for current research on Indonesia. The authors, all acclaimed international experts on Indonesia, focus on those areas that are particularly nettlesome for Indonesia's new leaders: the economy, religion and ethnicity, civil society, and the military. A concluding chapter is devoted to the International Monetary Fund and U.S. policy toward Indonesia. The result of their inquiries is a rich, forward-looking volume that provides a first glimpse into the future of Indonesia in the post-Suharto era.